2017
DOI: 10.1177/1833358317721305
|View full text |Cite
|
Sign up to set email alerts
|

Validity of routinely collected data in identifying hip fractures at a major tertiary hospital in Australia

Abstract: When it is not practical to use the algorithm for regular monitoring of HFs, using PD by admission to estimate total HFs and PD by episode in combination with a procedure code to estimate HFs with surgery can produce robust estimations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Keeping in mind that it was assessed by central recoders with their own potential biases, the overall quality of coding in our study was moderate, with significant variations between comorbidities (online supplementary table). Other studies for various specific indications such as venous thromboembolism,24 25 arrhythmia,26 stroke,27 hypersensitivity reactions,28 bone metastases,29 glaucoma,30 hip fractures,31 hidradenitis suppurativa,32 acute kidney injury,33 overdoses34 and sepsis19 35 have also found average validity, with significant variations between studies for the same condition 19 27 36. Under the French hospital payment system, patients with comorbidities are associated with higher payments to compensate for the higher burden of care, which may have favoured NPV over PPV and sensitivity over specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping in mind that it was assessed by central recoders with their own potential biases, the overall quality of coding in our study was moderate, with significant variations between comorbidities (online supplementary table). Other studies for various specific indications such as venous thromboembolism,24 25 arrhythmia,26 stroke,27 hypersensitivity reactions,28 bone metastases,29 glaucoma,30 hip fractures,31 hidradenitis suppurativa,32 acute kidney injury,33 overdoses34 and sepsis19 35 have also found average validity, with significant variations between studies for the same condition 19 27 36. Under the French hospital payment system, patients with comorbidities are associated with higher payments to compensate for the higher burden of care, which may have favoured NPV over PPV and sensitivity over specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first in Victoria to investigate hip fracture incidence and mortality using real-world administrative data. Limitations common with other administrative data studies include possible under-reporting of hip fractures [ 19 ], differential recording of diagnoses and admission sources, incomplete medical records, wrong dates of admission, discharge, and deaths. Data quality were maximized with regular Australian Government data integrity audits [ 45 ] and the quality of ICD-10-AM coding in Victorian hospitals was previously validated [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients aged 50 years or above and admitted to a public or private hospital for hip fracture (International Statistical Classification of Diseases and Related Health Problems, Tenth Revision, Australian Modification [ICD-10-AM] S72.0-S72.2) [ 7 , 17 - 19 ] and discharged between 1 July 2012 and 30 June 2018 were included. A previous Australian study demonstrated the sensitivity of hip fracture ascertainment from routinely collected administrative data was around 95% and the positive predictive value was above 70% [ 19 ]. Our study only looked at the first hip fractures and removed any patients with any previous history of hip fractures in the past 6 years.…”
Section: Methodsmentioning
confidence: 99%
“…Hip fracture is a major clinical event that almost always requires hospitalisation and is generally accurately coded. [17][18][19] The diagnosis codes to identify hip fracture are subject to local clinical practice; the sites will use their own standard or validated algorithms for identifying hip fracture. The algorithms for hip fracture used by each site, and positive predictive values where available, are provided in table 2.…”
Section: Outcome Assessmentmentioning
confidence: 99%